Food Security of Kuzbass Region Population in 1905-1907: Local Features - A. Y. Karpinets (Научный диалог, 2017)
The article is devoted to identification and characterization of regional characteristics of the First Russian revolution in the context of food security of the population by the example of Kuzbass region of 1902-1909. The main material served are the works by “pre-revolutionary” (A. S. Ermolov, V. M. Obukhov), “Soviet” (G. W. Buzurbaev, Z. G. Karpenko, etc.) and modern authors (S. V. Makarchuk, M. V. Shilovsky, etc.). The work demonstrates that a series of bad events in agriculture of the country European provinces contributed to the growth of social tension among the peasants. It is proved that acutely this was evident during the First Russian revolution of 1905-1907. Special attention is paid to the analysis of regional characteristics of the problem. The article evaluates and compares the level of food security of the population of European Russia provinces during the First Russian revolution and the food security of the population of Kuzbass region in the early 20th century. The impact of bad crop events on the depth of social protests among the peasants of Kuzbass region during the First Russian revolution is discussed. The relevance of the study is determined by the centenary of the Great Russian revolution.